A Short-lived Rejuvenation during the Decades-long Changing-look Transition in the Nucleus of Mrk 1018 - Kai-Xing Lu; Yan-Rong Li; Qingwen Wu; Luis C. Ho; Zhi-Xiang Zhang; Hai-Cheng Feng; Sha-Sha Li; Yong-Jie Chen; Mouyuan Sun; Xinwen Shu; Wei-Jian Guo; Cheng Cheng; et al. (The Astrophysical Journal Supplement Series)
Changing-look active galactic nuclei (CL-AGNs), characterized by the emergence or disappearance of broad lines accompanied by extreme continuum flux variability, have drawn much attention for their potential to reveal physical processes underlying AGN evolution. We perform seven-season spectroscopic monitoring on Mrk1018, one of the earliest identified CL-AGN. Around 2020, we detect a full-cycle changing-look transition of Mrk 1018 within one year, associated with a nucleus outburst, which likely arose from the disk instability in the transition region between the outer standard rotation-dominated disk and inner advection-dominated accretion flow. Over the past 45 years, the accretion rate of Mrk 1018 changed 1000 times and the maximum Eddington ratio reached 0.02. By investigating the relation between the broad-line properties and the Eddington ratio ( L _bol / L _Edd ), we find strong evidence that the full-cycle-type transition is regulated by accretion. There exists a turnover point in the Balmer decrement, which is observed for the first time. The broad Balmer lines change from a single peak in Types 1.0–1.2 to double peaks in Types 1.5–1.8, and the double-peak separation decreases with increasing accretion rate. We also find that the FWHM of the broad Balmer lines obeys FWHM $\propto \,{(L_{{\rm{bol}}}/L_{{\rm{Edd}}})}^{-0.27}$ , as expected for a virialized broad-line region (BLR). The velocity dispersion σ _line follows a similar trend in Types 1.5–1.8 but displays a sharp increase in Types 1.0–1.2, resulting in a dramatic drop in FWHM/ σ _line . These findings suggest that a virialized BLR together with accretion-dependent turbulent motions might be responsible for the diversity of BLR phenomena across the AGN population.